Crime and Mental Wellbeing - Andrew Leigh
Most estimates of the cost of crime focus on victims. Yet it is plausible that an even larger cost of crime occurs via its indirect impact on the mental wellbeing of non-victims. To test how crime affects individuals' mental outcomes, we exploit detailed panel data on mental wellbeing, allowing us to observe the relationship between changes in crime in a local area and changes in the mental wellbeing of resident non-victims in that area (controlling for changes in local economic conditions). Our results suggest that increases in crime rates have a negative impact on the mental wellbeing of residents, with the biggest impacts arising from violent crime. We also find that local press coverage of criminal activity enhances the effect of crime on mental well-being.neighbourhood effects, health, mental health, fear of crime